ALK receptor activation, ligands and therapeutic targeting in glioblastoma and in other cancers - Wellstein, Anton (Frontiers in Oncology, 2012)
The intracellular anaplastic lymphoma kinase (ALK) fragment shows striking homology with members of the insulin receptor family and was initially identified as an oncogenic fusion protein resulting from a translocation in lymphoma and more recently in a range of cancers. The full length ALK transmembrane receptor of approximately 220 kDa was identified based on this initial work. This tyrosine kinase receptor and its ligands, the growth factors pleiotrophin (PTN) and midkine are highly expressed during development of the nervous system and other organs. Each of these genes has been implicated in malignant progression of different tumor types and shown to alter phenotypes as well as signal transduction in cultured normal and tumor cells. Beyond its role in cancer, the ALK receptor pathway is thought to contribute to nervous system development, function and repair as well as metabolic homeostasis and the maintenance of tissue regeneration. ALK receptor activity in cancer can be upregulated by amplification, overexpression, ligand binding, mutations in the intracellular domain of the receptor and by activity of the receptor tyrosine phosphatase PTPRz. Here we discuss the evidence for ligand control of ALK actvity as well as the potential prognostic and therapeutic implications from gene expression and functional studies. An analysis of eighteen published gene expression data sets from different cancers shows that overexpression of ALK, its smaller homologue LTK (leukocyte tyrosine kinase) and the ligands PTN and MK in cancer tissues from patients correlate significantly with worse course and outcome of the disease. This observation together with preclinical functional studies suggests that this pathway could be a valid therapeutic target for which complementary targeting strategies with small molecule kinase inhibitors as well as antibodies to ligands or the receptors may be used.